AN UPDATED SURVEY OF MALESIAN SEED PLANTS FAMILIES - M.M.J. VAN BALGOOY (Research Center for Biology, 2010)
VAN BALGOOY,M.M.J. 2010. An updated survey of Malesian Seed Plants Families. Reinwardtia 13(2): 171-181. - The conservative family concept has been adopted on the Malesian Seed Plants Families I - III to show the visible characters to help identify specimen herbarium of the Malesian Plants. During a new classification of orders and families of flowering plants based on the molecular data has been leaded, some changes in family delimitation have occurred. By providing this family survey, the users of Malesian Seed Plants book can place their taxa in the correct family.